(untitled) (Tumou Tou: Jurnal Pengabdian Masyarakat, 2024)
Emergency First Response (EFR) or better known as Basic Life Support or first aid given to people experiencing an emergency. EMERGENCY FIRST RESPONSE is a subject matter given to students in the Underwater Ecotourism study program which aims to provide students with the knowledge and skills to become a responder who provides first aid in accidents. So as a form of community service, students implement this field activity in Darunu Village, Wori District or better known as Mangore Darunu Tourism Village, where this village is a fostered village of the Manado State Polytechnic, Department of Tourism in developing its tourism. Emergency First Response (EFR) needs to be trained for the community because as a tourist destination visited by various guests, it is necessary to know things about providing first aid if guests or the community themselves experience a medical emergency, because being a ’savior’ is not necessarily a doctor or paramedic, but literally anyone can do this, even those who do not have medical training: every citizen can be a ’savior’ when he intervenes to help others, while waiting for the arrival of more qualified assistance, such as medical personnel